1988
DOI: 10.1016/0021-9517(88)90146-7
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of platinum catalysts by oxygen 1. Kinetics of the catalyst deactivation

Abstract: Dijkgraaf, P.J.M.; Rijk, M.J.M.; Meuldijk, J.; van der Wiele, K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Oxidative removal of CO by molecular oxygen can minimize this difficulty. However, high surface oxygen concentration should be avoided to prevent the successive oxidation and thus deactivation of Pd, the so-called over-oxidation phenomenon. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative removal of CO by molecular oxygen can minimize this difficulty. However, high surface oxygen concentration should be avoided to prevent the successive oxidation and thus deactivation of Pd, the so-called over-oxidation phenomenon. …”
Section: Resultsmentioning
confidence: 99%
“…An important feature of the reaction is that too high an oxygen concentration can lead to excessive oxygen coverage of the active sites that diminishes the catalytic activity. This type of catalyst deactivation (termed as over-oxidation) , can simply be avoided by operating the reactor in the mass-transport-limited regime, where the surface reaction is not rate determining. , …”
Section: Introductionmentioning
confidence: 99%
“…In the liquid-phase oxidations of alcohols using supported metal catalysts such as Pt/carbon and Pd/carbon, molecular oxygen irreversibly deactivates the catalyst surfaces to form inactive surface metal oxides. 12b, Low catalytic activities of Pd/carbon or Pd/Al 2 O 3 in our oxidation of cinnamyl alcohol might be ascribed to such an irreversible poisoning of molecular oxygen onto the metallic surface of the small Pd particles. On the contrary, in the case of the giant Pd cluster, such an oxidation of Pd particles by molecular oxygen would be presumably prevented because of the slightly cationic Pd atoms on the cluster surface.…”
Section: Electronic Effectmentioning
confidence: 99%
“…The exact process by which the aldehyde forms is not known. Under basic conditions, it has been proposed that the alcohol becomes deprotonated in solution and undergoes hydride elimination on the catalyst surface to form the aldehyde. , This hypothesis has been disputed on the basis of the observation that oxidation also occurs under acidic conditions, and it has been proposed instead that the alkoxide is formed on the catalyst surface. , Other authors have suggested that it is the C–H bond that is broken first because of its lower bond strength. , …”
Section: Introductionmentioning
confidence: 99%